Networking the Learner 2002
DOI: 10.1007/978-0-387-35596-2_4
|View full text |Cite
|
Sign up to set email alerts
|

Social Presence Online: Networking Learners at a Distance

Abstract: This paper draws on two studies which researched the use of online small group environments where collaborative leaming is a central structure for leaming. The establishment of social presence is facilitated through the socioaffective aspect of small group interaction which contributed to the effectiveness of leaming online. Social presence, the ability of online leamers to project thernselves into a textual environment which has few visual or contextual cues, will be explored as an important elernent in facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 10 publications
2
32
0
4
Order By: Relevance
“…In addition, they had positive experiences of it because the teacher's own interest and enthusiasm about the subject could be better transmitted to students. This finding is similar to that of Stacey (2002), who found out that the teacher's "affective" behavior, including humor, emotion and self-disclosure, were a style of communication that appealed to students in online teaching.…”
Section: Student-centered Teaching and The Teacher's Enthusiasmsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, they had positive experiences of it because the teacher's own interest and enthusiasm about the subject could be better transmitted to students. This finding is similar to that of Stacey (2002), who found out that the teacher's "affective" behavior, including humor, emotion and self-disclosure, were a style of communication that appealed to students in online teaching.…”
Section: Student-centered Teaching and The Teacher's Enthusiasmsupporting
confidence: 86%
“…One of them is the lack of direct contact with the teacher and other students: as quite a bit of human interaction is actually non-verbal, online interaction becomes somewhat limited in this sense (Stacey, 2002;Tian, Yu, Vogel, & Kwok, 2011). In a pedagogical sense, online teaching necessitates various types of expertise from the teachers, too, such as paying attention to how differently communication happens in online environments compared to classroom interaction, and misunderstandings or misinterpretations may happen more easily (Wilson & Stacey, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many characteristics and factors that constitute social presence, this study relies on a conflation and expansion of many scholars' concepts (especially Ke, 2010;Stacey, 2002;Sung & Mayer, 2012) in order to make sense of what these specific students found to establish social presence. Initially, this research hypothesized that incorporating Voki avatars would significantly increase students' perceptions of social presence, but other factors seem to play a larger role.…”
Section: Discussionmentioning
confidence: 99%
“…Richardson and Swan (2003) found that the instructor was one of the most essential aspects when investigating students' perception of social presence. Likewise, Stacey (2002) found that the instructor's role was "a major factor" in the success of online learning. Ke (2010) examined social presence in online classes, specifically focusing on adult learners, finding that "teaching presence should be the catalyst that initiates the community development process" (p. 817).…”
Section: Instructor Presence and Immediacymentioning
confidence: 99%
“…Research has shown that social presence is one of the most significant factors in improving instructional effectiveness and building a sense of community. Research by Stacey [24] discovered that establishing social presence is an important aspect for effective online interaction and learning and found that a high quality of electronic communication helps to engage students and aids in their learning of the course material.…”
Section: Social Presence Theorymentioning
confidence: 99%